(untitled) - Tomlinson, P. B. (New York, 1994)
In addition to being a source of timber, mangroves--tropical plants growing in both marine and terrestrial environments--protect shorelines from wave damage and provide a nursery for many commercial fishes. This concise overview emphasizes the biology of individual species.
Keywords: Cây đước,Sinh thái học cây đước,Mangrove plants,Mangrove ecology